Persepsi Siswa terhadap Lingkungan Sekolah di SMK Taruna Padang - Sabrina, Sabrina; Jasrial, Jasrial (ANWARUL, 2024)
This research was motivated by the school environment which was not as good as expected by Taruna Padang Vocational School. The aim of this research is to obtain information regarding students' perceptions of the school environment at Taruna Padang Vocational School, which is seen from the aspects of school facilities, learning resources, learning media, teacher-student relationships and student-student relationships. Therefore, the problem that will be studied in this research is, "how good is the school environment at SMK Taruna Padang?". The type of research used was descriptive quantitative with the research population being students of class X and XI SMK Taruna Padang, totaling 125 students and a sample of 55 students. Samples were drawn using the Slovin formula and taken using random sampling techniques. From the results of data processing, the average score of students' perceptions of the school environment seen from the aspect of school facilities is 3.18 in the quite good category, the average score of students' perceptions of the school environment seen from the aspect of learning resources is 3.18 in the fair category. good, the average score of students' perceptions of the school environment seen from the learning media aspect is 3.24 in the quite good category, the average score of students' perceptions of the school environment seen from the aspect of the relationship between teachers and students is 3.71 in the good category, the score The average student perception of the school environment seen from the aspect of student-student relationships is 3.60 in the good category. From these results it can be concluded that students' perceptions of the school environment at Taruna Padang Vocational School are quite good with an average score of 3.38.